War by Other Means : Aftermath in Post-Genocide Guatemala - Nelson, Diane M., 1963-; McAllister, Carlota, 1969- (Book collections on Project MUSE., 2013)
In this collection of essays, leading scholars based throughout the Americas examine postwar Guatemalan society from varied perspectives, including those of ethnography, history, geography, politics, and economics.